Pengembangan Program Pemberdayaan Masyarakat melalui Penguatan Digitalisasi UMKM di Kota Manado - Jericho Pombengi; Joyce Rares; Jade Ratulangi; Meydian Lanipa; Monica Sinadia; Rivaldi Sebel (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
The current progress of digital transformation requires Micro, Small, and Medium Enterprises (MSMEs) to quickly adapt to these developments in order to remain competitive, particularly in the city of Manado, where the economy is dominated by the service sector. This study aims to conduct an in-depth analysis of community empowerment program development through the strengthening of MSME digitalization as a strategic step to bolster the local economy. Using descriptive qualitative methods and data from the 2025 Manado City Labor Statistics, this study explores the actual conditions where the service sector absorbs up to 68.89% of the workforce. The research findings indicate that empowerment programs begin by identifying key issues, such as low digital literacy, limited access to technology, and the challenges entrepreneurs face in adapting to digital market algorithms. During the implementation phase, non-formal technical training programs have successfully reached SME operators, particularly the “Self-Employed” group, which accounts for 22.65% of the workforce. Initiatives such as the Digital Entrepreneurship Academy offer training in digital marketing, e-commerce operational management, and the implementation of financial payment systems like QRIS. The evaluation indicates a positive impact on expanding market access and improving business efficiency, in line with the decline in the open unemployment rate in Manado to 8.51% by 2025. It is recommended that the local government expand the scope of training to other supporting sectors and digitally integrate MSME data so that assistance can be provided more evenly.